Periacinar retraction clefting in proliferative prostatic atrophy and prostatic adenocarcinoma - Ulamec, Monika (BMJ Group, 2007)
AIMS: To evaluate the presence and extent of periacinar retraction clefting in proliferative prostatic atrophy and carcinoma in radical prostatectomy specimens. METHODS: Atrophic foci and neoplastic glands were analysed in specimens from 50 patients who underwent radical prostatectomy. Analysed atrophic glands were classified in two main groups, proliferative atrophy (PA) and proliferative inflammatory atrophy (PIA); each group was subclassified into simple atrophy (SA) and postatrophic hyperplasia (PAH). According to the presence and extent of periacinar retraction clefting, atrophic and neoplastic glands were classified as: group 1, glands without clefts or with clefts affecting ⩽50% of gland circumference; group 2, glands with clefts that affected >50% of the circumference in <50% of examined glands; and group 3, glands with clefts that affected >50% of the circumference in ⩾50% of examined glands. RESULTS: Forty‐four (88.0%) atrophic foci were without periacinar clefts or clefts were present in less than half of the gland circumference (group 1). In 6 (12.0%), atrophic foci clefts affected >50% of gland circumference (groups 2 and 3). Forty‐five (90.0%) carcinomas were with clefts which affected more than 50% of gland circumference (groups 2 and 3); and in five carcinomas only, clefts were not found or affected <50% of gland circumference (group 1). CONCLUSION: Results indicate that periacinar retraction clefting represents a reliable criterion in differential diagnosis between proliferative atrophy and carcinoma.